Development of Logarithmic Equations for Statistical Sample Determination - Zaied, Moayad B; El Naim, Ahmed M; Mekki, Dafalla M (Journal of Empirical Studies, 2014)
Sample size estimation is a fundamental step in designing trials and studies for which the primary objective is the estimation or the comparison of parameters. In this paper, the equation of sample for proportion was used to develop two equations for sample size determination. The resultant equations are natural and normal logarithmic. The validation test was conducted for populations with different sizes from 10 to 100000 from which sample size was calculated applying the equation of sample for proportion, finite population correction for proportion equation and the developed equations at 0.05 and 0.01 levels of significance. It was found that the sample size calculated by natural logarithmic equation was larger than sample sizes calculated by proportion, finite population correction for proportion, and normal logarithmic equation. Sample size calculated by normal logarithmic equation was the smallest up to 1000 population size at 0.05 level of significance and up to 10000 population sizes at 0.01 levels.